Analysis of Jet Dynamics and Collimation Characteristics of 0241+622 on Parsec Scales - Haitian Shang; Wei Zhao; Xiaoyu Hong; Xu-zhi Hu (The Astrophysical Journal)
We conducted a detailed analysis of the jet structure and dynamics of the source 0241+622 on milliarcsecond scales. We stacked images from multiple epochs to better recover the cross section of the jet. By analyzing the relationship between jet width and distance, we observed that the jet exhibits a parabolic shape from the core, spanning a region from 0.12 to 6.1 mas. This structure suggests the acceleration and collimation processes of the jet. Beyond 18 mas from the core, the jet adopts a conical shape, and the expansion speed of the jet becomes faster within the range from 4500 to 6500 mas. We obtained the core shift of this source using five pairs of data from the Very Long Baseline Array at 1.6 to 43 GHz. Based on previous studies, through proper motion analysis of the jet components, we estimated the angle between the jet and the line of sight to be approximately 65 $\mathop{.}\limits^{\unicode{x000b0}}$ 7, so 1 mas corresponds to 0.95 pc (deprojected distance). We then obtained the velocity field of the source within 3.14 mas from the central black hole and found that the jet exhibits accelerated motion within this range. At approximately 6.1 mas from the core, we observed that the jet width begins to decrease, which we identified as possibly corresponding to the Bondi radius of this source. The reduction in jet width may be related to changes in the external environmental pressure, particularly within the Bondi radius, indicating that the jet dynamics and collimation characteristics are strongly influenced by the surrounding medium conditions.